Impact of Sarcopenic Obesity on Outcomes in Patients Undergoing Hepatectomy for Hepatocellular Carcinoma. Issue 5 (May 2019) - Kobayashi, Atsushi; Kaido, Toshimi; Hamaguchi, Yuhei; Okumura, Shinya; Shirai, Hisaya; Yao, Siyuan; Kamo, Naoko; Yagi, Shintaro; Taura, Kojiro; Okajima, Hideaki; Uemoto, Shinji
Abstract : Objective: To evaluate preoperative body composition, including skeletal muscle and visceral adipose tissue, and to clarify the impact on outcomes after hepatectomy for hepatocellular carcinoma (HCC). Background: Recent studies have indicated that sarcopenia is associated with morbidity and mortality in various pathologies, including cancer, and that obesity or visceral adiposity represents a significant risk factor for several cancers. However, the impact of sarcopenic obesity on outcomes after hepatectomy for HCC has not been fully investigated. Methods: We retrospectively analyzed 465 patients who underwent primary hepatectomy for HCC between April 2005 and March 2015. Skeletal muscle mass and visceral adipose tissue were evaluated by preoperative computed tomography to define sarcopenia and obesity. Patients were classified into 1 of 4 body composition groups according to the presence or absence of sarcopenia and obesity. Results: Body composition was classified as nonsarcopenic nonobesity in 184 patients (39%), nonsarcopenic obesity in 219 (47%), sarcopenic nonobesity in 31 (7%), and sarcopenic obesity in 31 (7%). Compared with patients with nonsarcopenic nonobesity, patients with sarcopenic obesity displayed worse median survival (84.7 vs. 39.1 mo, P = 0.002) and worse median recurrence-free survival (21.4 vs. 8.4 mo, P = 0.003). Multivariate analysis identified sarcopenic obesity as a significant risk factor for death (hazard ratio [HR] = 2.504, P = 0.005) and HCC recurrence (HR = 2.031, P = 0.006) after hepatectomy for HCC. Conclusion: Preoperative sarcopenic obesity was an independent risk factor for death and HCC recurrence after hepatectomy for HCC. Abstract : Supplemental Digital Content is available in the text